Genetic Ablation of Na,K-ATPase α4 Results in Sperm Energetic Defects - Numata, September; McDermott, Jeffrey P.; Blanco, Gustavo (Frontiers in Cell and Developmental Biology, 2022)
The Na,K-ATPase alpha 4 isoform (NKAα4) is expressed specifically in the male germ cells of the testes and is particularly abundant in mature spermatozoa. Genetic deletion of NKAα4 in mice (NKAα4 KO mice) results in complete infertility of male, but not female mice. The reduced fecundity of NKAα4 KO male mice is due to a series of defects, including a severe impairment in total and hyperactive sperm motility. In this work, we show that deletion of NKAα4 also leads to major defects in sperm metabolism and energetics. Thus, compared to wild-type sperm, sperm from NKAα4 KO mice display a significant reduction in the extracellular acidification rate (ECAR), indicative of impaired glycolytic flux. In addition, mitochondrial function is disrupted in sperm lacking NKAα4, as indicated by a reduction in the mitochondrial membrane potential and lower oxygen consumption rate (OCR). Moreover, the ratio between the oxidized and reduced forms of nicotinamide adenine dinucleotide (NAD/NADH) is increased in NKAα4 KO sperm, indicating a shift in the cellular redox state. These metabolic changes are associated with augmented reactive oxygen species (ROS) production and increased lipid peroxidation in NKAα4 KO sperm. Altogether, these findings reveal a novel link between NKAα4 activity and sperm energetics, highlighting the essential role of this ion transporter in sperm physiology.